Estudo da casca da raiz da espécie Maytenus ilicifolia Mart. ex Reissek, modificações estruturais do composto β-sitosterol e análises das atividades antimicrobianas - Copetti, Daniela (2016)
This dissertation describes the phytochemical study of Maytenus ilicifolia Mart species. ex Reissek belonging to Celastreceae family. Further, structural modification reactions were performed in β-sitosterol compound, in order to carry out a study of structure / activity against strains of micro-organisms. Through the root bark collected in the municipality of Santana do Livramento - RS was obtained crude extract methanol which gave different subfractions according to the polarity, as it was possible to isolate 4 secondary metabolites. In addition reactions were carried out using acetic anhydride, succinic anhydride and phthalic anhydride to obtain various derivatives of the metabolite isolated β-sitosterol. Ending with analysis of the antimicrobial activity of extracts, fractions and isolated compounds derived from β-sitosterol, carried out by microdilution method plates, opposite to five Gram-positive bacteria, six gram-negative and seven fungi. It was observed in this analysis that the extracts, fractions and isolated metabolites tested showed good results mainly against bacteria Enterococcus and Shigella sonnei, and front the fungus Candida krusei and Cryptococcus neoforman. In the study of structure / activity it has been observed that the addition of two carbolines β-sitosterol contribute to antimicrobial activity.